A mixed-method investigations of work, government and social factors associated with severe injuries in artisanal and small-scale mining (ASM) operations - Ajith, Michael; Ghosh, Apurna; Jansz, Janis (Elsevier, 2021)
The susceptibility of miners to severe injuries in Artisanal and Small-scale Mining (ASM) operations is significantly higher than in the larger-scale mining industry. However, the most prevalent and least studied safety aspects are the factors affecting the severe injuries and miners’ awareness of the state of their health and safety. Severe injuries are ASM-related injuries that have resulted in more than two weeks lost workdays. This paper aims to demonstrate that severe injuries in ASM industry do not occur simply due to individual personality but also because of other underlying factors like ignorance of illegality of the activity. The paper also reports on the injured miners’ perception of the nature of health and safety. Two hundred and thirty-six miners from Migori County of Western Kenya ASM site were administered closed-ended structured survey questionnaires, followed by face-to-face qualitative interview of thirty-three severely injured mineworkers identified from the quantitative survey respondents. The survey results were analysed using logistic regression. While the interview results were subjected to thematic analysis, the identified themes confirmed or complemented quantitative findings as well as demonstrated the state of occupational health and safety (OHS) in ASM industry. The results showed that alcohol and drug usage, inadequate earnings, safety training, lack of hazard identification and risk control measures, lack of safety equipment, poor management-miners interaction, poor communication of safety concerns, and government support were indicators of poor safety culture influenced the recurrence of severe injuries. Research outcomes will support decision-making processes and implementation of programs in this industry.